Development of digital learning media based on the GlideApps website on geography subjects endogenous power material - Fakhruddin, Mohammad Thofiqo; Sahrina, Alfi; Utomo, Dwiyono Hari; Deffinika, Ifan (Jurnal Inovasi Teknologi Pendidikan, 2024)
The research was driven by the limited implementation of technology and the lack of interesting geography learning media on endogenous material. Abstract and complex material requires media that can visualize events resulting from endogenous forces. Based on these problems, the right form of technology utilization is the media website GlideApps supported with images and animations. The research aims to produce a website-based learning media and a proper application of endogenous materials. This type of research is Research and Development with a 4-D development model, namely: Define, Design, Development, and Decimate. This media validation test is based on the assessment of media expert validators and material experts. Evaluation of product validation results by media expert validators was 98.75% (valid), and material experts 80% (valid enough). In addition, implementation was carried out for subject teachers and students, and the results showed a positive response because the media presented material that was more interesting, easily accessible at any time, and made learning not boring supported by various features so that it increased the enthusiasm and activeness of students in participating in learning activities.